The reverse congruency effect elicited by eye-gaze as a function of attention-deficit/hyperactivity disorder symptoms - Chacón-Candia, Jeanette A.; Ponce, Renato; Marotta, Andrea (Frontiers in Psychology, 2024)
Individuals diagnosed with attention deficit/hyperactivity disorder (ADHD) have been found to have impairments in multiple aspects of social cognition, thus including the attentional processing of socially relevant stimuli such as eye-gaze. However, to date, it remains unclear whether only the social-specific but not the domain-general directional components, elicited by eye-gaze are affected by ADHD symptomatology. To address this issue, the present study aimed to investigate the impact of ADHD-like traits on the social-specific attentional processing of eye-gaze. To this purpose, we conducted an online experiment with a sample of 140 healthy undergraduate participants who completed two self-reported questionnaires designed to assess ADHD-like traits, and a social variant of an interference spatial task known to effectively isolate the social-specific component of eye-gaze. To make our research plan transparent, our hypotheses, together with the plans of analyses, were registered before data exploration. Results showed that while the social-specific component of eye-gaze was evident in the sample, no significant correlation was found between this component and the measured ADHD-like traits. These results appear to contradict the intuition that the attentional processing of the social-specific components of eyegaze may be impaired by ADHD symptomatology. However, further research involving children and clinical populations is needed in order to clarify this matter.